2000
DOI: 10.7557/3.2969
|View full text |Cite
|
Sign up to set email alerts
|

First independent feeding of harp seal (<i>Phoca groenlandica</i>) and hooded seal (<i>Cystophora cristata</i>) pups in the Greenland Sea

Abstract: Data were collected from harp seal (Phoca groenlandica) and hooded seal (Cystophora cristata) pups belonging to the Greenland Sea (or "West Ice") stocks in 1995-1997. Pups of both species were observed to feed independently shortly after weaning, and their first food was almost exclusively crustaceans. Parathemisto sp., particularly P libellula, dominated the diet of both the harp and the hooded seal pups, but the diet also contained sympagic amphipods of the genus Gammarus. Krill (Thysanoessa sp.) was of mino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Hooded seals have long been known to co-occur with harp seals in the drift ice waters of the Greenland Sea along the east coast of Greenland during spring, when both species breed (March/ April: see Wollebaek 1907;Iversen 1927;Rasmussen 1957;Folkow & Blix 1995;Folkow et al 1996Folkow et al , 2004Haug et al 2000;Potelov et al 2000). Recent information, obtained in satellite tagging programmes, about the migratory patterns of the two seal species indicate that they may also co-occur in the Greenland Sea pack ice outside the breeding period (Folkow et al 1996(Folkow et al , 2004.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hooded seals have long been known to co-occur with harp seals in the drift ice waters of the Greenland Sea along the east coast of Greenland during spring, when both species breed (March/ April: see Wollebaek 1907;Iversen 1927;Rasmussen 1957;Folkow & Blix 1995;Folkow et al 1996Folkow et al , 2004Haug et al 2000;Potelov et al 2000). Recent information, obtained in satellite tagging programmes, about the migratory patterns of the two seal species indicate that they may also co-occur in the Greenland Sea pack ice outside the breeding period (Folkow et al 1996(Folkow et al , 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Hooded seals, Cystophora cristata, occur in the drift ice waters of the Greenland Sea along the east coast of Greenland (also called the West Ice) during breeding and moult (March/April; see Rasmussen 1957Rasmussen , 1960Folkow & Blix 1995;Folkow et al 1996;Haug et al 2000;Potelov et al 2000). Recent information about the migratory patterns of the species obtained in satellite tagging programmes has indicated that hooded seals may also occur in the Greenland Sea pack ice in considerable periods outside the breeding and moulting period (Folkow et al 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pups leave the pack-ice at approximately 1 mo of age and lead a solitary pelagic life for the subsequent months, visiting distant foraging areas (Folkow et al 2010), resembling the pattern of adults (Folkow et al 1996). The diet of a hooded seal pup during the first month consists almost exclusively of crustaceans (Haug et al 2000). Later, for older seals, when associated with the pack-ice, the diet consists of prey species found at greater depths (Haug et al 2004, with no apparent differences in prey composition between young (< 2 yr) and older seals ).…”
Section: Discussionmentioning
confidence: 99%
“…Haug,K. T. Nilssen & L. Lindblom,Institute of Marine Research,Tromsø Branch,Box 6404,Norway,tore.haug@imr.no. Harp (Phoca groenlandica) and hooded (Cystophora cristata) seals co-occur in the drift ice waters of the Greenland Sea along the east coast of Greenland during breeding and moulting (March-June; see Sergeant 1991;Folkow & Blix 1995;Folkow et al 1996;Haug et al 2000;Potelov et al 2000). In this area, previous studies of the two species have concentrated mainly on stock size estimation, reproduction and migration patterns (Øritsland 1959, 1964Øien & Ørits-land 1995;Folkow & Blix 1995, 1999Folkow et al 1996;ICES 1998ICES , 2004Frie et al 2003;Folkow et al 2004).…”
mentioning
confidence: 99%